Theories and Theoria of the Atonement: A Proposal - Johnson, Adam J. (International journal of systematic theology, 2021)
This article traces the origins of language about ‘theories’ of the atonement in Friedrich Schleiermacher and F.C. Baur’s historicization of Protestant theology in Germany. It follows the growth and promulgation of this conceptualization as it spread to America and Great Britain in the later nineteenth century. This approach contributed to the growth and development of the doctrine and its history, while severely limiting it in important ways. I note four dangers implicit within uncritical use of ‘theory’ language in studies of the history of the doctrine of the atonement, and conclude by arguing that a more fitting approach lies in the ancient and medieval concept of theoria, or contemplation, which serves as the broader telos for appreciating the riches we have in the work of Christ, within which modest contemporary notions of theory can and should play a role.